Voice of Customer sebagai Strategi Peningkatan Customer Value Berbasis Syariah - Silvia Ripa Nurkaromah; Mariatul Ulfah; Shinta Puja Rinjani; Abdhi Adiansyah (SIL'AH: Jurnal Ekonomi Syariah, 2026)
This study aims to describe the role of Voice of Customer (VoC) as a corporate strategy in enhancing customer value through the effectiveness of Customer Relationship Management (CRM) and Sharia-based customer satisfaction. This study employs a descriptive approach.. The data was obtained from scientific literature relevant to the research topic. The data analysis technique was conducted through the stages of data reduction, data presentation, and conclusion drawing. The findings indicate that VoC plays an important role in helping companies understand customer needs and expectations through various forms of customer feedback. In addition, VoC supports innovation development, improves the effectiveness of Sharia CRM, and strengthens Sharia-based customer satisfaction through improvements in service quality, customer experience, and emotional relationships with customers. The findings of this study confirm that the implementation of VoC can be aligned with the principles of Islamic economics, namely trustworthiness, honesty, transparency and customer welfare, in business activities.